MAKNA SIMBOLIK SESAJEN DALAM KESENIAN TRADISIONAL KUDA LUMPING SANGGAR KARYA BUDAYA DI DESA KEMUNING MUDA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Susanti, Ria Putri; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Kuda lumping is one of local cultural assets that owned by the Indonesian people and must preserved. In this art sesajen is one of the elements that can not be separated. In the sesajen in kuda lumping by Karya Budaya group, there are some symbolic aspects that have certain meaning is represented from the attributes and sesajen activities performed by the handler and kuda lumping toward sesajen. The purpose of this study is to know the meaning of physical symbols, social situation and social interaction of sesajen in the traditional art kuda lumping by Karya Budaya group at Kemuning Muda Village. This research uses qualitative research method with Symbolic Interaction approach. The informants in this research are the kuda lumping masterpiece of Karya Budaya, the trainer of kuda lumping of Karya Budaya, the senior and junior players of kuda lumping of Karya Budaya also the kuda lumping audiences which are selected purposively. Data collection techniques are conduted through in-depth interviews, observation and documentation. The results of this study indicate that the symbolic meaning of sesajen in the kuda lumping art of Karya Budaya at Kemuning Muda Village Bunga Raya Subdistrict Siak Regency consists of physical symbols that include people offer in the sesajen it self such as incense, chicken ingkung, pisang raja, snacks, rice pulut, egg, cassava flower, drink, rice, crackers, peyek, lalaban, tubers, pencok bakal, white rice and tempe bacem, comb, powder, mirror and lipstick, yellow rice, ketupat, dadap leaf, mermaid and young coconut with certain meanings every part. The social situation of the offerings in the art of the kuda lumping of Culture consists of the chants of prayer (mantra) read by the handler, incense burning by the handler, sow yellow rice by the handler and eat the offerings by the kuda lumping players of Karya Budaya which also have a certain meaning. The meaning of social interaction products include the meaning of sesajen from the handler's, from the coach, from the side of the kuda lumping by Karya Budaya group and from the viewer art of kuda lumping art show.